Belajar Bersama Alam Berbasis Qur'an : Strategi Menumbuhkan Rasa Ingin tahu Siswa Kelas II Madrasah Ibtidaiyah Alam Ya Bunayya Bungo - Futri Monika Ningsih; Muhammad Solihin; Ulfa Adilla (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2026)
This research is motivated by the low curiosity of grade II students of Madrasah Ibtidaiyah, which is still characterized by a passive attitude, dependence on teachers' explanations, and limited courage to ask questions in the learning process. This study aims to describe the application of Qur'an-based learning together, analyze its role in fostering students' curiosity, and identify the supporting and inhibiting factors of its implementation. The research uses the Classroom Action Research approach with the Kemmis and McTaggart model, which includes planning, action execution, observation, and reflection. The subject of the study was a second-grade student of Madrasah Ibtidaiyah Alam Ya Bunayya Bungo, with data collection techniques in the form of observation, interviews, documentation, and field notes. The results of the study show that the Qur'an-based learning strategy can be applied systematically through the use of the environment as a learning resource, the integration of Qur'anic verses, and the use of experimental methods. This strategy has been proven to foster students' curiosity, which is seen in increased attention, courage to ask questions, activeness in observing, and involvement in learning activities. The success of the implementation is supported by an adequate learning environment, teacher readiness, and an open learning atmosphere, although obstacles in the form of passive learning habits and technical obstacles in the field are still found. It was concluded that Qur'an-based learning with nature was effectively developed as a contextual and spiritual learning strategy to foster the curiosity of madrasah ibtidaiyah students.